Antiproliferative activity of Grewia villosa ethyl acetate extract on cervical cancer HeLa cell line: Mechanistic insights through network pharmacology and functional assays approach - Sally Wambui Kamau; Mercy Jepkorir; Gilbert Kipkoech; Inyani John Lino Lagu; Wesley Kanda; Susan Kibunja; Rakita Letoluo; Shadrack Barmasai; Alice Wanyoko; Vincent Ruttoh; James Kuria; Peter Githaiga Mwitari; et al. (PLoS ONE, 2025)
Grewia villosa is a plant native to Kenya, with a traditional history among Ambeere people for treating and managing prostate and breast cancers. Previous scientific studies have demonstrated its anti-inflammatory and antioxidant properties. However, a scientific gap exists on the bioactivity of G. villosa against cervical cancer, particularly on in vitro HeLa cell line model. Additionally, the specific molecular targets and mode of antiproliferative action have not been well elucidated. Therefore, this study sought to investigate the antiproliferative activity, putative targets and mode of action of G. villosa using in vitro cell culture, molecular biology and in silico-based approaches. Antiproliferative analyses were evaluated through MTT assay, cell migration inhibition through in vitro scratch assay, and phytochemical profiling through Gas chromatography-mass spectrometry (GC-MS) analysis. Further, putative targets were identified through network pharmacology approach, computationally validated by molecular docking, and functionally through the real-time quantitative polymerase chain reaction (RT-qPCR) method. The G. villosa ethyl acetate (GVEA) extract fraction was the most active extract fraction, with IC50 of 100.7 µg/mL and a selectivity index of 2.38. Dodecan-2-ylbenzene and 2,6,10-trimethyltetradecane compounds were some notable compounds that can partly be associated with reported antiproliferative activity as they demonstrated strong binding affinity to identified putative targets, including EGFR and AKT1. RT-qPCR analysis functionally confirmed the downregulation of EGFR and AKT1, and the upregulation of tumor protein 53 and Caspase 3 molecular targets, suggesting that GVEA extract indeed perturbs the predicted molecular targets. This study therefore reports the selective antiproliferative properties of the G. villosa ethyl acetate extract fraction in a cervical cancer model (HeLa) cell line while at the same time providing putative targets, which is important in shedding light on potential mechanistic basis of its demonstrated antiproliferative activity. This highlights the plant’s potential in discovering products and compounds for further investigation on possible application in cervical cancer management and/or treatment.